هزرى ناسیونالیزم له شیعرى کوردى (حاجی قادرى ک ۆیی) بهنموونه - ابه, شوان سلێمان ی (Sulaimani Journal for Humanities, 2021)
Nationalism historical phenomenon of intellectual, political and social of great importance, in recent centuries has had a major role in directing the events of the life of nationalities. These is by preserving heritage and national identity and has an important dimension, a subjective state with sensitivity of a group living in the geographical boundaries of a clear and well known, and speak a common language. Therefore literature and the fact that women reflection of the life of society, is considered a major reason for the awareness and the progress of society , so determine the sex and identity of the foundations and the specifics Nationalism in the field of literature in general and particularly in the Kurdish literature , is an act of useful and valuable . In this research we tried to identify and show the beginnings of thought Nationalism in Kurdish literature and especially poetry Kurdish , and chose the poetry ( Haji Kadri koyi ) as an example because he was a poet melted and merged with the National Nationalism thought and tried to step his people Kurdish along with the world's peoples the other in this area.